Tourism Development in The Berawa Beach in The Village of Tibubeneng Badung Bali Indonesia - Kartimin, I Wayan; Sunarta, I Nyoman; Sudiarta, I Nyoman; Nuruddin (International Journal of Psychosocial Rehabilitation, 2020)
This article discusses the development of tourism activities in Berawa Beach in the Village of Tibubeneng, North Kuta District, Badung Regency. Determination of Berawa Beach as a tourist attraction began in 2005 based on Badung Regent Regulation No. 7 of 2005 dated 7 February 2005. This research uses descriptive qualitative research methods with the method of finding data through documentation, literature review, interviews and observations. The locus of research is around the Berawa Beach Area by extracting data on observations of the object’s environment, discussions with stakeholders and interviews with tourists. The results of this study indicate that in a relatively short period of time, the dynamics of tourism in the Berawa Coastal Region experienced a significant development. This is evidenced by the large number of foreign investors entering there and the tourism facilities at Berawa Beach are oriented towards meeting international tourists.